Owalne tempietta w małej architekturze sakralnej w Polsce - Bania, Zbigniew (TECHNE. Seria Nowa, 2018)
The most commonly applied compositional motif in Polish Baroque altarsis an aedicula, variously transformed – in the Berninian spirit – with an intermittent or curved finial, and multiple side pillars. I believe that it would be advisable to distinguish a set of solutions that stem from the idea Francesco Borromini applied while designing the bays within the pillars of the nave in the Archbasilica of St. John [in] Lateran in Rome. This composition refers to the concept of tempiettoson a circular plan, and the modification there lies in its extensive transformation: lowering the frontal pillars, and giving it an oval plan with an intermittent finial. Thus, what we have there is an attempt to design a pillared canopy that opens towards the interior of the church and which contains either sculptures or a painting composition.